The Influence of Stabilizers on Brucella abortus RB51 - Hafez, Amani A.; elsalam , sally M.abd; Donia, Gehad R.; mohammed, Rasha.S; Helmy, Noha A. (International Journal of Psychosocial Rehabilitation, 2020)
Brucella abortus is one of the most important pathogenic brucella species, RB51 B.abortus vaccine is the best available vaccine used to control and prophylactic of brucellosis, RB51 is live attenuated lyophilized vaccine during freeze drying the bacterial cells exposed to stress due to the lypholization steps which overcomes by using of stabilizers that added to protect the bacterial cells from this stress. Therefore this study was conducted to evaluate the efficacy of skimmed milk and WHO as stabilizing compounds for preparation of B.abortus RB51 vaccines and evaluate their humoral and cellular immunity by immunizing the mice with the prepared vaccines .the sera samples were tested by I-ELISA assay and the spleen samples were measured for IFN-Ɣ as indicator of cellular immunity then, the results were compared with the licensed RB51 vaccine.